Value of transoesophageal echocardiography-guided approach to electrical cardioversion of atrial fibrillation - O. S. Kalashnikovа (Zaporožskij Medicinskij Žurnal)
Electrical cardioversion (ECV) of atrial fibrillation (AF) may be associated with thromboembolism. For thromboembolism prevention both transoesophageal echocardiography (TOE) performed for left atrial thrombi detection and anticoagulation with oral anticoagulants (OAC) for 3 weeks before cardioversion are recommended, but there is lack of clinical evidence for real efficiency of such anticoagulation.